Language policy changes in Malaysia : democracy at work? - Tharmalingam, Selvarajah (2012)
Malaysia gained its independence from the British in 1957. It practices parliamentary democracy with a constitutional monarch as the supreme head of the country. The parliament, under the leadership of a prime minister and elected representatives, is the legislative authority for Malaysia. The parliament passes Federal laws, examines the government’s policies, approves the government’s expenditures and approves new taxes. It also serves as the forum for debate and deliberations; and the focus of public opinion on national affairs. In Malaysia, issues related to language are always treated carefully because it is deemed to be sensitive. Bahasa Malaysia (BM) is the mother tongue of the Malays (the majority group) and the national language while English, being the language of international communication, is officially the second language. (A number of Chinese and Indian languages are also spoken, and officially acknowledged.) In 1971, Bahasa Malaysia was made the medium of instruction in all national schools, supplanting English medium ones. After three decades of the Malay-only policy, Malaysia, a largely trading nation, realised that the proficiency level of English among Malaysians has deteriorated to the point of almost halting its globalisation policy. This was considered a huge setback in the push towards becoming a fully developed country by the year 2020. Sensing the weakness, the Malaysian government, to shore up declining standards in English, announced that the teaching of Mathematics and Science would be conducted via the English language (English for Teaching Mathematics and Science - ETeMS). The policy was implemented in January 2003 in all government schools in Malaysia. The decision to teach these vital subjects in English language triggered substantial reaction from all levels of the public, and split the nation into several factions, each lying at various points on the “totally against - totally for” continuum. As a result of this decision, hundreds of citizens shared their opinion on the issue mainly through the mainstream media. This paper addresses the issue whether or not the policy makers take into account the views of the public before making a final decision on language policy matters. The paper also addresses the issue of whether linguistic analyses can reveal the true nature of public opinion as displayed through their writings in the media, and especially whether the analyses answer the following questions: Does the policy makers consider the general public’s views in shaping/ implementing a language policy? Is English detrimental to the status of Malay as the official language of Malaysia? To gather data, the study investigates three mainstream newspapers; Utusan Malaysia, The Star and The Sun and three online portals, Malaysiakini, Malaysian Insider and Malaysia Today, in order to assess the media discourse of Malaysians over a two-year period. The study utilises an analytical framework that includes Critical Discourse Analysis by incorporating the “Discourse Historical” approach to critical analysis. The findings reveal not only the public’s perception of the language policy changes but also provide significant information on the direction and success of the language policy.